A Review on Hydroxyapatite: Properties, Its Composite, and Its Slow-Release Fertilizers Application - Hemzah, Sabila Aulia; Noviyanti, Atiek Rostika; Kurnia, Irwan; Hardian, Arie; Irwansyah, Ferli Septi; Ma’Amor, Azman (Jurnal Kartika Kimia, 2025)
Hydroxyapatite (HAp), a natural mineral form of calcium apatite, has recently received significant attention due to its potential application as a slow-release fertilizer. This review aims to comprehensively analyze HA and its composites, focusing on properties, synthesis methods, and nutrient release mechanisms in agricultural applications. HA's high biocompatibility, excellent adsorption capacity, and ability to release nutrients gradually make it an ideal candidate for increasing soil fertility and crop yields. This review also explores the incorporation of other materials, such as urea, carboxylated cellulose, and montmorillonite, to form HA composites, thereby increasing their efficiency as fertilizer. In addition, the environmental benefits of using HA-based fertilizers, such as reduced nutrient leaching and improved soil health, were also investigated. Challenges and future perspectives are also discussed, emphasizing the need for further research to optimize these materials for practical agricultural use. This review highlights the potential of HA and its composites to revolutionize sustainable agriculture by providing a controlled and efficient nutrient release system.